Mechanisms of Electing Akims as a Tool for Increasing the Democracy of Local Self-Government in the Republic of Kazakhstan - Kaliyev, И.А.; Serikbayeva, А.Т. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article examines the process of electing akims as a factor in the democratization of society. The purpose of the article is to update the processes of decentralization as a priority area of state policy to strengthen the management system in the Republic of Kazakhstan. The article analyzes the experience of the transition from indirect to direct elections of district akims in a city, a city of regional significance, a village, a village, a rural district. The prospects for the implementation of amendments to the electoral legislation of Kazakhstan regarding the upcoming direct elections of akims of districts of the city of regional significance have been determined. The research methodology is based on an analytical cluster and consists of a systematic, comparative, predictive, and content analysis of the mechanisms of akim election. The results of the study allow us to assess the compliance of the model of appointment and election of akims with the principles of integrity of democratic initiatives. The commitment of the country's leadership to the principle of a "listening state" in reforming the local government system is pointed out. The importance of choosing a planned liberal format for increasing the democracy of local government, which meets the requirements of modern socio-cultural realities and cultural and historical traditions of the people of Kazakhstan, is being actualized. The conceptual components of the process of electing mayors provide for: exact compliance with the Constitution of the Republic of Kazakhstan and the laws governing the election of mayors; updating the initiatives of the country's leadership to improve the process of forming local government bodies; responding to requests from the local community regarding the regulation of the electoral process. The mechanisms of organizing elections to local government bodies and their comparison with similar models in neighboring and far-abroad countries are determined. It is noted that the norms of the electoral legislation of the Republic of Kazakhstan must comply with the recommendations of the United Nations and the OSCE in the area of decentralization of power. In general, the holding of the 2021 elections and the constitutional amendments in 2022 marked the beginning of an improvement in the process of electing mayors and formed the basis for a full transition to direct elections of local governments. The prospects of the study focus on the issue of differentiation of electoral legislation in relation to akims of different levels and on the unification of the electability of all akims, including regions, cities of republican significance and the capital.